2022
DOI: 10.3390/su141912054
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Innovations in Rural Communities of Developing Countries II—Causal Network and Leverage Point Analyses of Transformations

Abstract: Solving complex system challenges such as natural resource management in social-ecological systems (SESs) is fraught with great uncertainty. To cope with these challenges, socially vulnerable people in developing countries have created various autonomous innovations. This study focuses on the concept of leverage point (LP) to understand the emergence of innovations and the transformation mechanism of SESs. An LP is a part of a complex system where a small change can cause transformations in the entire system a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Thus, the continued emergence of autonomous innovations among socially vulnerable people, especially in developing countries, will facilitate the transformation of social-ecological systems. Tajima, et al (2022) found that autonomous innovations starting from motivations closer to everyday life could produce by-products of collective actions that promote public value enhancement [19]. They argued that this process was important to the emergence of innovations that could address wicked problems.…”
Section: Autonomous Innovations Emerging Among Socially Vulnerable Pe...mentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the continued emergence of autonomous innovations among socially vulnerable people, especially in developing countries, will facilitate the transformation of social-ecological systems. Tajima, et al (2022) found that autonomous innovations starting from motivations closer to everyday life could produce by-products of collective actions that promote public value enhancement [19]. They argued that this process was important to the emergence of innovations that could address wicked problems.…”
Section: Autonomous Innovations Emerging Among Socially Vulnerable Pe...mentioning
confidence: 99%
“…Takemura et al (in press) have developed an analytical method for LP identification using causal network analysis. They also clarified that LPs were classified into three types with different characteristics [27]. Since this method is based on causal relationship chains, it allows us to analyze the function of LPs in the emergence of innovations along the time series in detail.…”
Section: Application Of the Leverage Point Lensmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, sustainability requires a decision-making support system that not only considers current opinions and benefits but also future visions [22]. Third, in the case of complex social-ecological systems (SES), a linear approach toward a specific goal or future vision may not adequately address uncertainty [23].…”
Section: Introductionmentioning
confidence: 99%